KEWENANGAN ISTRI DALAM PENGGUNAAN HARTA SUAMI MENURUT FIQH AL-SYAFI’IYAH - Asnawi (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2022)
This study is very interesting because it explains the position of the husband's property and how the provisions for the use of the wife against the husband's property according to Fiqh Al-Syafi'iyyah. This research is a library research with a descriptive qualitative research type through a normative approach, using a documentation data collection technique, while the data analysis uses a transferability technique. The results of his research that the position of the husband's assets obtained during marriage can be categorized as joint assets between husband and wife which are included in the concept of syirkah abdān or syirkah muwafadlah. According to Fiqh Al-Syafi'iyyah, the use of a wife against her husband's property is not permissible without the permission of the husband. However, if the husband gives permission or the wife knows that the husband allows his wife to take only what is rightfully hers, then the wife may take and use it. This is because the husband's personal property is wholly owned by the husband, even though some of the property belongs to the wife. Unlike the case with husband and wife syirkah assets, where they can use it as much as their respective rights in the property.